Early Bifrontal Brain Injury: Disturbances in Cognitive Function Development - Christine Bonnier; Aurélie Costet; Ghassan Hmaimess; Corinne Catale; Christelle Maillart; Patricia Marique (Neurology Research International)
We describe six psychomotor, language, and neuropsychological sequential developmental evaluations in a boy who sustained a severe bifrontal traumatic brain injury (TBI) at 19 months of age. Visuospatial, drawing, and writing skills failed to develop normally. Gradually increasing difficulties were noted in language leading to reading and spontaneous speech difficulties. The last two evaluations showed executive deficits in inhibition, flexibility, and working memory. Those executive abnormalities seemed to be involved in the other impairments. In conclusion, early frontal brain injury disorganizes the development of cognitive functions, and interactions exist between executive function and other cognitive functions during development.